Police and the liberal state - Dubber, Markus Dirk; Valverde, Mariana (Critical perspectives on crime and law)
Introduction : policing the Rechtsstaat / Markus D. Dubber and Mariana Valverde -- Police, sovereignty, and law : Foucaultian reflections / Mariana Valverde -- The supreme sovereignty of the state : a genealogy of police in American constitutional law, from the founding era to Lochner / Christopher Tomlins -- Police power and the hidden transformation of the American state / William J. Novak -- Limited liberty, durable patriarchy / Mark E. Kann -- Criminal police in the Rechtsstaat / Markus D. Dubber -- Work and authority in policing / David Alan Sklansky -- The elusive line between prevention and detection of crime in German undercover policing / Jacqueline E. Ross -- Vulnerability, sovereignty, and police power in the ASBO / Peter Ramsay -- Loitering in the city that works : on circulation, activity, and police in governing urban space / Ron Levi